Problematic issues of the effectiveness of treatment of patients with chronic viral hepatitis C according to the State program and the ways of their solution. - Shostakovych-Koretska, L. R.; Shevchenko-Makarenko, O. P.; Tymofyeyeva, L. V.; Tkachenko, V. D. (Medicni Perspektivi, 2018)
The authors present the experience of antiviral treatment of patients with chronic viral hepatitis C (HVHC) within the framework of the State Target Social Program for the Prevention, Diagnosis and Treatment of Viral Hepatitis until 2016 and the local program "Population Health of Dnipropetrovsk Region for 2015-2019". The authors reviewed the treatment regimens that can be used in patients according to the latest recommendations of WHO and international organizations on the study of the liver (EASL, APASL and AASLD). The authors discussed the problematic issues of the effectiveness of treatment regimens containing interferon and ribavirin, as well as interferon-free regimens of therapy. At the first stage of the work, the authors noted the coverage of with antiviral therapy of HVHC patients in the Dnipropetrovsk region, taking into account the patients followed up the Unified electronic registry of patients of adult age with chronic viral hepatitis B, C and B + C. 3875 patients are included in the register, 3334 have HVHC, of them – 2795 patients with viremia. Antiviral therapy was received by 1038 patients with chronic viral hepatitis, including those with HVHC – 912 patients. In 2017, 725 people with HVHC completed antiviral therapy, the coverage of treatment was 21.75% of the total need, based on the number of patients in the Registry. As a result of treatment, 22 patients with the 1st genotype of HCV, had failed therapy with interferon-containing regimens. However, in a detailed analysis, the authors found that in one case there was a reinfection with another HCV genotype. Relapse was determined in 14 (63%) patients, partial virological response in 3 (14%) patients and non-response in 4 (23%) patients. At the second stage of the work, the re-treatment regimen was evaluated in patients with treatment failure after the use of PEG-IFN regimens using interferon-free regimens containing direct-acting antiviral drugs (DAA) for 12 weeks in 21 patients with an average age of 42.4±2.89 years, with the 1st HCV genotype, with an average disease duration of 6.52±1.05 years. There were 14 men with a mean age of 39.67±4.16 years and 9 women with a mean age of 46.22±4.01 years. The level of fibrosis: F1 – 8 people, F2 – 7, F3 – 3 and F4 – 3. 3D treatment regimen was used for retreatment including the following: Ombitasvir / Paritaprevir / Ritonavir + Dasabuvir + Ribavirin (3D+RBV) in 16 patients, moreover, 3 of them had compensated liver cirrhosis. 5 patients with HCV genotype 1 without the presence of liver cirrhosis were given the following scheme: Ledipasvir + Sofosbuvir + Ribavirin (SOF+LDV+RBV). All patients had a sustained virological response (SVR-24) and the effectiveness of the antiviral therapy was rated as 100%. Also two clinical cases of treatment of HVHC in patients with antiviral therapy failure are presented. For further implementation of the WHO strategy for the elimination of viral hepatitis, it is necessary to continue the work on the formation of the Registry of patients with chronic viral hepatitis in order to improve the provision of care to patients in this category. Further study of the issue of personalization of antiviral therapy and minimization of risks that adversely affect its results are required.